The comfort of the mystics : a manual and anthology of early Sufism - Böwering, Gerhard, 1939- (Islamic History and Civilization, 2013)
This critical Arabic text edition of Salwat al-ʿārifīn wa-uns al-mushtāqīn, a manual of early Sufism by Abū Khalaf al-Ṭabarī (d. circa 470/1077), is based on a very old manuscript preserved in Dār al-Kutub al-Miṣrīya of Cairo, Egypt and copied in 459/1067. It is introduced by a detailed analytical study of the author and his work. Salwat al-ʿārifīn forms an integral part of Sufi literature and reflects Islamic developments in Nishapur in northeastern Iran. This crucial Arabic text, published for the first time, is especially valuable because of its great philological accuracy and sound textual tradition. It represents an essential source for the intellectual history of Islam during the middle of the 4th/10th to the middle of the 5th/11th century.